Wage and Employment Rates in New Zealand from 1991 to 2001 - Guyonne Kalb; Rosanna Scutella (New Zealand Government, The Treasury, 2003)
This paper presents results for five separately estimated sets of employment and wage equations. The New Zealand working- age population is divided into sole parents, single men, single women, married men and married women. The results for the wage equations are as anticipated and similar to the results in other countries. A higher education level, living in a city and age (up to the early forties) increase the expected wage. Wages also differ significantly across industries and occupations. Employment follows the expected patterns as well, where women with children are less likely to be employed; education increases the employment probability; and living in remote areas decreases employment. In addition to the usual variables, unemployment affects the probability of employment negatively and a clear upward time trend is observed for sole parents, living with one's parents decreases the employment probability of singles but increases the probability for sole parents, and eligibility for the New Zealand Superannuation seems relevant in the employment decision.
Keywords: J21; J31; 330; Wage rate; employment; joint model specification